MEMAKNAI KASUNDAAN SENIMAN KARAWITAN SUNDA TAN DESENG - Santi Susanti; Iwan Koswara (Yayasan Akrab Pekanbaru, 2019)
This paper aims to reveal the experience of Tan Deseng, a Sundanese musical artist of Chinese descent, in interpreting the kasundaan he lived. This paper is based on the existence of Chinese descendants who behave in a Sundanese, even more Sundanese than the Sundanese themselves. The qualitative method of phenomenology is used for the collection and analysis of data in revealing Tan Deseng's experience to live as a Sundanese. The results showed that Tan Deseng lives as a Sundanese with all its aspects, from the Sundanese language, Muslim, married to Sundanese, philosophy of life, to the arts as the identity of a Sundanese. According to the criteria of a Sundanese, it can be said that Tan Deseng is a Sundanese subjectively and socio-culturally.